Analisis Implementasi Model Kepemimpinan Profetik Di Perguruan Tinggi Muhammadiyah (Studi Kasus Universitas Muhammadiyah Semarang) - Setia Iriyanto; Edy Purwanto (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Background - The concept of the Islamic leadership model cannot be separated from the leadership that has been carried out by the Prophets and Messengers of Allah SWT. This leadership model is often referred to as prophetic leadership. Muhammadiyah University Semarang (Unimus) is one of the Muhammadiyah Colleges based on Islamic education that has experienced very rapid progress. This is related to the leadership factor. Aim - Knowing the views and implementation of the prophetic leadership model at the Muhammadiyah University of Semarang Design / methodology / approach - Field research (field research) with qualitative methods. Collecting data with literature study, interviews, observation and documentation. As for data analysis with reduction, presentation and withdrawal of data conclusions with validity techniques using data triangulation. Finding - Unimus leadership in carrying out university development programs, one of which is the midnight prayer movement for the academic community. This program is believed to be an inner and outer endeavor. The view of prophetic leadership is in line with the application of the principles of Good University Governance (GUG), namely Shidiq (Honest), Amanah (Accountable), Tabligh (Transparency) and Fathonah (visionary). the principle of The Right Man in The Right Place. Aspects of liberation regarding work and applying the principles of asah, compassion and care and aspects of transcendence regarding worship activities (Islamic spirit) in Unimus Conclusion - The views and implementation of prophetic leadership have been carried out well within the Unimus academic community. The implementation of 3 aspects, namely the aspects of humanization, liberation and transcendence are defined as work, work and worship. Research Implications - This research is an overview of prophetic leadership that has been carried out and can be used as a reference in the development of other tertiary institutions. Limitations - The scope of this research is still limited to Unimus where the number of PTM/A in Indonesia is 172 and it is still qualitative in nature so it needs to be on a larger scale and in the form of quantitative research.